Pardes, Empat Tingkat Penafsiran Kitab Ibrani: Menimbang Sod Sebagai Penafsiran Esoterik Yang Mengundang Polemik - Yehuda Indra Gunawan; Abraham Pontius Sitinjak (STTI Harvest Semarang, 2021)
Pardes (sometimes written as 'PaRDeS') represents an abbreviation for: Peshat, Derash, Remez, and Sod apart from having different levels of search for meaning, but also unique in their way of interpretation. The advent of Pardes' hermeneutics has given direction to the world of Jewish hermeneutics. Pardes was the benchmark for hermeneutics in the Jewish tradition. Pardes becomes the standard in the steps of interpretation, mainly to examine the literary structure of the biblical text by considering the text as a whole based on their source language and combining relevant secondary and tertiary (third) background materials. Yet many theologians consider Sod, the highest level for interpreting the